2011
DOI: 10.1590/s0365-05962011000600036
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clinicoepidemiológico dos melanomas cutâneos em duas instituições de referência na cidade de Manaus, Brasil

Abstract: O conhecimento da frequência e das características clinicoepidemiológicas do melanoma cutâneo nas diversas regiões do Brasil é importante para avaliar a magnitude do problema e direcionar adequadamente as ações de saúde. Neste estudo, revisaram-se os dados de 55 pacientes com melanoma cutâneo atendidos em duas instituições de saúde da cidade de Manaus. Verificou-se maior frequência entre homens pardos, na oitava década de vida, com lesões do tipo melanoma acrolentiginoso nos membros inferiores, com Breslow mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, in the north of Brazil, a previous study reported that the predominant subtype is acral lentiginous melanoma and most patients are non-white. 20 Further, there is a predominance of studies on the south of the country, while studies on the north and northeast are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the north of Brazil, a previous study reported that the predominant subtype is acral lentiginous melanoma and most patients are non-white. 20 Further, there is a predominance of studies on the south of the country, while studies on the north and northeast are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, detailed population-based data on the incidence of CM according to demographic and histological characteristics are scarce. 25 Deficiency of compulsory notification, lack of reliable central registration, and lack of priority by public health managers are pointed out as the main barriers to a better understanding of the problem and the implementation of control actions. 25 …”
Section: Introductionmentioning
confidence: 99%